The use of special exercises in the preparatory period of skiers (Bangladesh Journal of Medical Science, 2024)
Background: Recently, there has been a tendency to decrease the results of  domestic  skiers,  in  order  to  solve  this  problem,  it  is necessary to change the training approach in the preparatory period before the competition.The purpose of the study: Improving  the  physical  fitness  of  skiers  using  special training tools.Materials and methods: In  the  Russian  Federation,  a  pedagogical  experiment  was conducted  in  the  village  of  Korshik.  It  was  attended  by teenagers  aged  13-14  who  were  engaged  in  cross-country skiing.  A  total  of  40  children  participated  (20-control  and 20-experimental  groups).  The  difference  between  the experimental  group  was  the  use  of  special  exercises  at the  preparatory  stage  of  training.  The  study  used  control standards  that  show  the  level  of  physical  qualities,  such  as pull-ups,  squats,  long  jumps,  simulated  100m  lifting  and 500m running.Results: The  children  from  the  experimental  group  significantly improved  their  performance  in  the  pull-up  test  (22.2%; p